Dietary pomegranate by-product improves oxidative stability of lamb meat. (April 2020) - Natalello, Antonio; Priolo, Alessandro; Valenti, Bernardo; Codini, Michela; Mattioli, Simona; Pauselli, Mariano; Puccio, Mario; Lanza, Massimiliano; Stergiadis, Sokratis; Luciano, Giuseppe
Abstract: This study investigated the effect of including whole pomegranate by-product in lamb diet on meat oxidative stability. Seventeen lambs were assigned to two experimental treatments and fed a cereal-based concentrate (CON) or the same concentrate where 200 g/kg DM of cereals were replaced by whole pomegranate by-product (WPB). Meat from WPB-fed lambs had a greater concentration of vitamin E (α- and γ-tocopherols), polyunsaturated fatty acids (PUFA), highly peroxidizable PUFA and a higher peroxidability index ( P  < .05). Feeding WPB limited the formation of metmyoglobin ( P  = .05) and reduced lipid oxidation (TBARS values) after 7 days of storage for raw meat ( P  = .024) or 4 days for cooked meat ( P  = .006). Feeding WPB increased meat antioxidant capacity (ORAC assay) in the lipophilic fraction ( P  = .017), but not in the hydrophilic. These results suggest that vitamin E in the pomegranate by-product contributed to the higher antioxidant capacity of meat from the WPB-fed lambs. Highlights: The inclusion of 20% whole pomegranate by-product (WPB) in lamb diet was evaluated. WPB is rich in bioactive compounds ( e.g. conjugated FA, vitamin E and phenols). WPB-lamb meat contained higher concentration of vitamin E and PUFA. Lipid oxidation and metmyoglobin formation of meat were reduced by WPB treatment. Dietary WPB increased the meat antioxidant capacity in the lipophilic fraction.